Training on Quizizz and Kahoot Learning Innovation as Learning Media for Teachers of SMAN 1 Papar, Kediri District - Ro'ufah Inayati; Mukhlis, Imam; Istiqomah, Ni’matul; Annisya’ (Prospect Publishing, 2024)
The aim of this community service activity is to improve the ability of teachers, especially those in Kediri Regency, to use Quizizz and Kahoot learning media to achieve learning goals. This activity was carried out using the Technical Assistance method in the form of Training and Workshop through 2 (two) stages, namely the first stage focused on socialization and delivery of the use of the Quiziz and Kahoot applications and the second stage focused on mentoring and FGD (Focus Group Discussion) practice in creating learning media on the Quizizz application and Kahoot as a learning medium. Evaluation of this activity is carried out during the training activity and looking at the final product of the activity. The aspects evaluated are attendance, participant activity, and participant understanding of the material that has been provided. The result of this activity is that there is an increase in the ability of teachers to utilize Quizizz and Kahoot learning media. Some teachers still experience problems in using this learning media, so further training and assistance is needed for teachers to maximize the results of this activity. The importance of mastering learning media by teachers aims to maximize learning activities in the classroom considering that nowadays the average student and teacher already has adequate devices for learning media, so with this phenomenon it is very important for teachers to be able to utilize existing technology to run activities smoothly. learning.